1973
DOI: 10.1002/macp.1973.021700106
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the initiating activity of (C2H5)3O+PF for the polymerization of N‐vinylcarbazole

Abstract: S U M M A R Y :In the presence of (CZH5)30fPF6 (1) N-vinyl carbazole (NVC) can polymerize rapidly and completely especially in methylene dichloride. A study of this polymerization, with 14C-labelled (C2H5)30+PFZ and with living p3lytetrahydrofuran as apparent initiators, has shown that oxonium ions are not responsible for the initiation. The true initiator is most probably PF, formed by the decomposition of the salt. The necessary co-initiator is provided by an impurity in the monomer. The initiation by a solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…is an important polymer owing to its electrophotographic applications [ 1 ]. The polymerization of N-vinylcarbazole (NVC) has been carried out by different types of catalytic agents such as free radicals [2][3][4], cations [5][6][7][8][9], Ziegler-Natta catalysts [10,11], and transition metal chlorides such as WC16 and MoCl5 [12]. It has been reported that the stereoregularity of poly(NVC) depends on the polymerization catalyst and conditions [13].…”
Section: Introduction Poly(n-vinylcarbazole)mentioning
confidence: 99%
“…is an important polymer owing to its electrophotographic applications [ 1 ]. The polymerization of N-vinylcarbazole (NVC) has been carried out by different types of catalytic agents such as free radicals [2][3][4], cations [5][6][7][8][9], Ziegler-Natta catalysts [10,11], and transition metal chlorides such as WC16 and MoCl5 [12]. It has been reported that the stereoregularity of poly(NVC) depends on the polymerization catalyst and conditions [13].…”
Section: Introduction Poly(n-vinylcarbazole)mentioning
confidence: 99%
“…Turchi et a1. 12 reported that polymerization of NVCa in the presence of triethyloxonium hexafluorophosphate yielded polymers with molecular weights greater than lo6. They proposed phosphorous pentafluoride instead of the commonly known oxonium ion as the possible active initiator responsible for rapid polymerization of NVCa.…”
Section: Introductionmentioning
confidence: 99%